Austin Harrison and the English review - Vogeler, Martha S.; ebrary, Inc. (Columbia : University of Missouri Press, 2008)
"Examining Austin Harrison as editor--his writings and opinions, his public life and relations--Vogeler offers a new perspective on British literary culture and political journalism in the years just before, during, and after the First World War and traces complex relationships between a son and his famous father"--Provided by publisher.
A positivist beginning, 1873-1898 -- The Berlin years, 1898-1905 -- The Northcliffe years, 1905-1910 -- At the English review, 1910-1914 -- Renewing the English review, 1910-1914 -- Continuity and change, 1910-1914 -- The great adult review, 1910-1914 -- The English review's war, 1914-1918 -- Postwar politics, 1918-1923 -- Postwar literature, 1918-1923 -- After the English review, 1923-1928.
Includes bibliographical references (p. 295-302) and index.
Electronic reproduction.
Keywords: Harrison, Austin, -- 1873-1928.; English review (London, England : 1908); Journalists -- Great Britain -- Biography; Periodical editors -- Great Britain -- Biography; Electronic books